The Role of the Bali Provincial Regional Development Bank Sanur Sub-Branch in Strengthening MSMEs Through People's Business Loans - Dewi, Putu Bintang Listya; Wirantari, I Dewa Ayu Putri (Lenggogeni Data Publishing, 2026)
The People's Business Credit Program (KUR) channeled through Regional Development Banks (BPD) serves as a strategic instrument in supporting the growth of Micro, Small, and Medium Enterprises (MSMEs) and strengthening regional economies. This study aims to analyze the extent to which the Sanur Branch Office of Bank BPD Bali contributes to MSMEs, as well as to identify the role of KUR distribution in enhancing business productivity and income. The research employs a qualitative approach, with data collection techniques including interviews, literature reviews, and document analysis. Results indicate that Bank BPD Bali Sanur Branch Office plays a significant role as a financing facilitator for MSMEs and as a bridge between government programs and local MSME needs. KUR distribution by Bank BPD Bali has proven effective in boosting MSMEs growth and development. The study affirms that optimizing the role of Bank BPD Bali in the KUR program is key to sustainably strengthening the foundation of Micro, Small, and Medium Enterprises.